Isolation of two Giardia lamblia (WB strain) clones with distinct surface protein and antigenic profiles and differing infectivity and virulence. - Udezulu, I A (1992)
To determine the relationship between antigenic profiles and pathogenicity among Giardia lamblia clones (WB strain), trophozoites were cloned by the technique of limiting dilution. The phenotype of each clone was determined by an indirect immunofluorescence test using a polyclonal rabbit anti-G. lamblia trophozoite serum made against the parent strain. Two clones were chosen for further studies: a highly fluorescent clone, F+, in which more than 95% of the trophozoites fluoresced, and a low-fluorescence clone, F-, in which fewer than 5% fluoresced. Sodium dodecyl sulfate-polyacrylamide gradient gel electrophoresis and enzyme-linked immunotransfer blot studies of the membrane fractions of the two clones and parent strain revealed differences in both the total protein and antigenic profiles. A serum cytotoxicity test with the polyclonal serum showed that the F+ clones were more susceptible to immobilization and killing, while the majority of cells of the F- clones were resistant to such killing. Assessment of the infectivity of the two clones in the Mongolian gerbil animal model indicated that the F- clone more readily initiated infections, produced more cysts, had a higher intestinal trophozoite load, and produced a more severe clinical syndrome, while the F+ clone was less phenotypically stable in vivo and in some cases took longer to be cleared from the intestine.